Assessing learner's differences in field dependence-independence cognitive ability using multi-metric methods - Nisiforou, Efi (Department of Multimedia and Graphic Arts, Faculty of Fine and Applied Arts, Cyprus University of Technology, 2016)
The notion that usersʾ characteristics such as cognitive ability have an effect on visual information processing is fast emerging. Henceforth, understanding how cutting-edge technologies can detect these cognitive abilities leads to solutions that improve users' online experiences. Complex cognitive processes function in the way people perceive visual information, while various neural pathways are involved. This PhD thesis investigated cognitive and creative processes to provide feedback towards the improvement of future Human-Computer Interaction (HCI), Technology-Enhanced Learning (TEL) and Personalised Learning Environments (PLEs). Taking the concept of interdisciplinary study as a fundamental principle, this research stands at the crossroads of rich bi-directional and reciprocal interactions between die disciplines of HCI (User Experience). Neuroscience. Psychology and Education Field Dependence-Independence (FD-I) is an important dimension of cognitive abilities through which individuals process information, classified through die conventional psychometric method Hidden Figures Test (HFT). Formed based on individual's reliance on the context to extract specific meaning, it encompasses three distinct approaches: Field- Dependence (FD). Field-Independence (FT) and Field-Neutral or Mixed (FN/FM). Field-Dependent learners find it difficult to identify a simple geometric figure embedded in a complex image; Field-Independents can identify- the separate parts of a whole: and Field-Neutrals behave as FD or FI according to die learning situation. The Torrance Test of Creative Thinking (TTCT) was employed to measure individuals' level of creativity. A total sample of one hundred and twenty-nine (n=129) students were sourced across the experiments and was recruited from public universities in Cyprus and the United Kingdom A multi-metric method approach was employed and combined valid and reliable existing psychometric methods with biometric (ET) and neurometric techniques (EEG) in order to comprehend aspects of the visual processing system, involving: a) psychometric tests to measure learners' cognitive abilities and creativity, b) eye movement analysis through eye-tracking (ET) metrics, and c) brain signals via electroencephalography (EEG) measurements. The empirical and experimental methods used are mainly quantitative estimations that provide continuous, objective measurements of human-system interactions. Eye movements were recorded during a set of visual tasks with the aid of the SMI iViewX eye-tracker device; and brain activation was measured with the use of the mBrainTraining Smarting EEG device. The findings highlighted the effectiveness of eye-tracking and EEG as potential techniques in detecting users' cognitive ability during visual processing. The psychometric, biometric and neurometric methods were statistically examined, demonstrating a relationship between users' FD-I cognitive ability, creativity, eye gaze behaviour and brain signals. The psychophysiological data revealed individual differences m users' FD-I visuospatial attention, saccadic and fixation eye movements, creativity, and reaction time during the visual search tasks. Differences have also been identified among the FD-I visuospatial groups in die Occipital and Frontal brain regions. Hence, as technologies continue to develop, it is imperative to understand how to design interfaces and instructional materials that support the specific needs and preferences of learners (i.e. individual information-processing and/or disembedding capabilities). Therefore, this work has revealed a number of research contributions for adaptive and personalised learning systems. The proposed method of assessing and evaluating FD-I and creativity using psychophysiological signals is one of the main contributions of this project. On the basis of the new method employed this research attempted to map out the complex phenomenon of individual differences in Field Dependence-Independence cognitive processing with psychophysiological traits (creativity, eye movements and brain activity-). This work has publicised, for die first time to our knowledge, apparent proof that the FD-I construct affects users eye movements as a valid enmeshed contributory determinant. Eventually, die findings aimed to suggest a set of principles based on the eye-movement behaviours and brain signals (EEG) derived during the process of experiments. Consequently, concepts have been encapsulated based on different disciplines in a novel research setting in the HCI community, contributing with knowledge on how user differences manifest themselves during certain visual tasks. Finally, limitations and implications for future directions of research and practice are addressed.
Keywords: Field Dependence/Independence; Hidden Figures Test; Cognitive abilities; Higher education; Learners; Eye-tracking; Eye movements; Fixation and saccades; Visual stimuli; Creativity; Torrance Test of Creative Thinking; EEG/ERP; Brain activation